First-principles investigation of the effect of Cr/(Ti+Cr) ratio on the structure and mechanical properties of Al-rich Al0.6875Ti0.3125-xCrxN coatings. (1st June 2023) - Xian, Lijun; Li, Lin; Fan, Hongyuan; Xian, Guang; Zhao, Haibo
Abstract: Aluminum-rich Al0.6875 Ti0.3125- x Cr x N coatings with different Cr/(Ti + Cr) ratios (0%, 20%, 40%, 60%, 80%, 100% respectively) are investigated using first principles methods based on density functional theory. The results show that the structural stability of the Al0.6875 Ti0.3125- x Cr x N coating decreases with the increase of Cr/(Ti + Cr) ratio. Al0.6875 Ti0.125 Cr0.1875 N (Cr/(Ti + Cr) = 80%) and Al0.6875 Ti0.0625 Cr0.25 N (Cr/(Ti + Cr) = 100%), with maximum bulk modulus, have the highest hardness (44 GPa). In addition, the analysis of band structure, density of states and charge density difference reveals that, with the increase of Cr/(Ti + Cr) ratio, the Al–N covalent bond strength is weakened while the metallic bond strength of the coating is enhanced, indicating that toughness of the Al0.6875 Ti0.3125- x Cr x N coating is enhanced. With respect to the Al0.6875 Ti0.125 Cr0.1875 N (Cr/(Ti + Cr) = 60%) coating, the effect of metallic bond strength is the most evident. Thus Al0.6875 Ti0.125 Cr0.1875 N coating, with the largest H 3 / E 2 value (0.54), owns the best toughness and plastic deformation resistance. Highlights: Stability of Al0.6875 Ti0.3125- x Cr x N decreases with Cr/(Ti + Cr) increasing. Metallicity of Al0.6875 Ti0.3125- x Cr x N increases with Cr/(Ti + Cr) increasing. Al0.6875 Ti0.125 Cr0.1875 N has the largest H 3 /E 2 value and best toughness.